2019
DOI: 10.1055/s-0038-1641171
|View full text |Cite
|
Sign up to set email alerts
|

The Relation of the Extracranial Spinal Accessory Nerve to the Sternocleidomastoid Muscle and the Internal Jugular Vein

Abstract: The spinal accessory nerve (SAN) exhibits variant anatomy in its relation to the internal jugular vein (IJV) as well as the sternocleidomastoid muscle (SCM). These variations are important in locating the nerve during surgical neck procedures to avoid its inadvertent injury. These variations, however, are not conserved among different populations and data from the Kenyan setting are partly elucidated. This study, therefore, aims to determine the variant anatomical relationship of the SAN to the SCM and IJV in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…There have been many attempts within the literature to describe the course of the spinal accessory nerve and to define its point of entry into the posterior triangle of the neck in relation to surrounding structures [8]. This includes distance from the clavicle [8,9], the mastoid process [3,4,8,11,12,23], the angle of the mandible [23], the greater auricular nerve [21] as well as, similar to this study, the distance along the posterior border of sternocleidomastoid from its superior insertion point [1,2,13,21,22].…”
Section: Discussionsupporting
confidence: 52%
“…There have been many attempts within the literature to describe the course of the spinal accessory nerve and to define its point of entry into the posterior triangle of the neck in relation to surrounding structures [8]. This includes distance from the clavicle [8,9], the mastoid process [3,4,8,11,12,23], the angle of the mandible [23], the greater auricular nerve [21] as well as, similar to this study, the distance along the posterior border of sternocleidomastoid from its superior insertion point [1,2,13,21,22].…”
Section: Discussionsupporting
confidence: 52%
“…The flow chart of the strategy used in this search is presented in Figure 1. A total of 25 studies ( n = 1346 heminecks, n = 798 subjects) were included in the final analysis, spanning a time from 1986 to 2023 (Table 1) (Abakay et al, 2020; Amirlak et al, 2020; Amuti et al, 2019; Anehosur et al, 2021; Aramrattana et al, 2005; Caliot et al, 1989; Chen et al, 2009; Dailiana et al, 2001; Diop et al, 1987; Durazzo et al, 2009; Ellis et al, 2023; Khavanin et al, 2019; Kierner et al, 2000; Krause et al, 1991; Lu et al, 2002; Peck & Luce, 1988; Raikos et al, 2017; Salgarelli et al, 2009; Shiozaki et al, 2007; Soo et al, 1986; Symes & Ellis, 2005; Tubbs et al, 2005; Vargas et al, 2009; Vathana et al, 2007; Wirth et al, 2011). Twenty‐two studies were cadaveric ( n = 1206 heminecks), and three studies were prospective intraoperative ( n = 140 heminecks).…”
Section: Resultsmentioning
confidence: 99%
“…Then it passes to the JF where it receives some fibers from the cranial root. The SAN exits the JF with the ninth and tenth cranial nerves as well as the internal jugular vein (IJV) [2][3][4].…”
Section: Anatomic Relationship Between the Spinal Accessory Nerve And...mentioning
confidence: 99%
“…al conducted a study in 181 and 80 ND, where the SAN was located medial to the IJV in 104(57.4%) and 68(85%), and lateral to the IJV in 72(39.8%) and 12(15%) of the cases respectively. [6,17] Few previous studies have reported on the incidence of the SAN passing through the fenestrated IJV. Hollinshead reported identifying 3.2% during cadaver dissection, Prades et.…”
Section: Diagnosis Of Different Pathologiesmentioning
confidence: 99%
See 1 more Smart Citation